A Study of Success Factors in Green Supply Chain Management in Manufacturing Industries in Malaysia - Mohd Rozar, Norlinda; Wan Mahmood, Wan Hasrulnizzam; Ibrahim, Abdullah; Razik, Md Ashlyzan (Journal of Economics, Business and Management, 2015)
Environmental issues have become a notably prevalent concern for governments, societies and business organizations. With environmental problems such as global warming, ozone depletion, solid waste and air pollution, business organizations are considered to be the source of most of the environmental problems. In Malaysia, manufacturing industry is one of the main contributors for the economic growth. Unfortunately, it has been caused for environmental deterioration. (DOE, 2013). In order to investigate further understand GSCM among manufacturers in Malaysia, This study has carry out survey to 241 of 522 certified companies MSISO 14001 in Malaysia is 522 companies. One of the results are consistent with the study of Rao (2007) who found that there is a manufacturing company that cannot sell and distribute raw materials internally to other companies or external use as raw material and subject to confidentiality policies. It is the raw material control gives a competitive edge in the market, especially in industries